Unveiling Charge Transport and Degradation Mechanisms of Aqueous Zn|α‐MoO3 Batteries in Conventional Concentration and Water‐in‐Salt Electrolytes: A Multi‐Modal In Situ and Operando Study. Issue 29 (4th September 2022) - Dunkin, Mikaela R.; Kuang, Jason; Yan, Shan; King, Steven T.; Housel, Lisa M.; Ma, Lu; Ehrlich, Steven N.; Okasinski, John S.; Takeuchi, Kenneth J.; Takeuchi, Esther S.; Marschilok, Amy C.; Wang, Lei
Abstract: Herein charge storage and transport properties are elucidated and cell degradation mechanisms of rechargeable aqueous Zn|α‐MoO3 batteries in three electrolyte systems (3 m ZnSO4, 3 m ZnCl2, and 30 m ZnCl2 [12.5 m ] water‐in‐salt (WIS)) are distinguished by a combination of in situ X‐ray diffraction (XRD), in situ X‐ray absorption spectroscopy (XAS), operando optoelectrochemistry, and operando energy dispersive X‐ray diffraction (EDXRD). In conventional concentration 3 m electrolytes, in situ XRD and XAS, as well as ex situ scanning transmission electron microscopy data collectively support Zn 2+ as the primary charge carrier. In addition, these systems are susceptible to cathode dissolution, Zn corrosion coupled with the hydrogen evolution reaction, and the resultant formation of basic zinc salt phases. The multi‐modal in situ and operando experimental analyses validate facile H + intercalation and extraction in concentrated 30 m ZnCl2 WIS electrolyte. Via operando EDXRD, reaction front and charge transport limitation during discharge and charge in the viscous WIS electrolyte are spatially tracked. This work provides new insight into the stability and degradation mechanisms of aqueous zinc batteries during static storage and upon dynamic cycling, and highlights the utility of in situ and operando techniques in understanding the superior stability of WIS electrolytes. Abstract : This work presents in‐depth characterization of charge storage and cell degradation mechanisms of Zn|α‐MoO3 batteries in 3 m ZnSO4, 3 m ZnCl2, and 30 m ZnCl2 water‐in‐a‐salt electrolytes. Ex situ scanning transmission electron microscopy, in situ X‐ray diffraction and X‐ray absorption near‐edge spectroscopy, as well as, operando optoelectrochemical and energy dispersive X‐ray diffraction are used to probe these battery configurations.